Conceitos de computação reconfigurável com aplicação prática em hardware didático - ARAÚJO, Carla Cristina da Cruz (2020)
The computation reconfigurable is as an intermediate solution among the solutions in hardware and software, with objectives, goals and motivations related with the acting improvement, flexibility, generality, efficiency, cost and other. This work has as the objective the creation of a tutorial of the parallel description language VHDL with practical applications in didactic hardware, introducing the concept of the model of computation Reconfigurable. The work presents the characteristics, basic concepts and peculiarities of the parallel description language VHDL, putting in practice with laboratories that increase the degree of difficulty as the student goes if adapting the language, at the end the student should develop an application that consists of a traditional game of the decade of seventy call Pong, the development of this application is done using the knowledge acquired over the course of practical labs work.